2016
DOI: 10.18608/jla.2016.32.12
|View full text |Cite
|
Sign up to set email alerts
|

Sleepers' Lag – Study on Motion and Attention

Abstract: Body language is an essential source of information in everyday communication. Low signal-to-noise ratio prevents us from using it in the automatic processing of student behaviour, an obstacle that we are slowly overcoming with advanced statistical methods. Instead of profiling individual behaviour of students in the classroom, the idea is to compare students and connect the observed traits to different levels of attention. With the usage of novel techniques from the field of computer vision, we focus on featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
(26 reference statements)
0
15
0
1
Order By: Relevance
“…Until less invasive technologies become available, alternative strategies and sources of information will have to be adopted. Raca, Tormey and Dillenbourg (2014) studied attention through a camera system, instead of through eye‐tracking or a wristband, to measure the reaction times of students listening to a lecture. The authors observed that inattentive students have later reactions than focused students.…”
Section: Resultsmentioning
confidence: 99%
“…Until less invasive technologies become available, alternative strategies and sources of information will have to be adopted. Raca, Tormey and Dillenbourg (2014) studied attention through a camera system, instead of through eye‐tracking or a wristband, to measure the reaction times of students listening to a lecture. The authors observed that inattentive students have later reactions than focused students.…”
Section: Resultsmentioning
confidence: 99%
“…They found that immediate neighbors had a significant influence on a student's attention, whereas students' motion was not directly connected with reported attention levels ). Furthermore, Raca et al (2014) analyzed students' reaction time upon presentation of relevant information (sleeper's lag). In addition to estimating head pose, they considered the class period, student's row, how often faces were automatically detected (as a precursor to eye contact), head movement, and the amount of still time (i.e., 5-s periods without head movement) because these features had previously been shown to be good predictors of engagement in learning (Raca et al 2015).…”
Section: Using Machine Learning To Assess Visible Indicators Of (Dis)mentioning
confidence: 99%
“…1 The classroom is the system. Above, the classroom is the output (Lantern, Alavi and Dillenbourg 2012); below, the classroom is the input (Raca et al 2014) Trend 2: Less Semantic…”
Section: Trend 1: More Physicalmentioning
confidence: 99%
“…abstractions of raw data, and these features do actually convey some semantics. For instance, Raca et al (2014) estimated the global level of learners' attention in a lecture room by placing two cameras in front of students. The ratio of co-movements (students rotating their head in a near-synchronous way) predicted self-estimated attention levels.…”
Section: Trend 1: More Physicalmentioning
confidence: 99%